2021
DOI: 10.3389/fpubh.2021.689919
|View full text |Cite
|
Sign up to set email alerts
|

Staff SARS-CoV-2 Seroprevalence and Mental Health as Key Factors in University Response to COVID-19 Pandemic

Abstract: Background: In response to rapid global spread of the newly emerged coronavirus disease 2019 (COVID-19), universities transitioned to online learning and telework to decrease risks of inter-person contact. To help administrators respond to the COVID-19 pandemic and better understand its impacts, we surveyed SARS-CoV-2 seroprevalence among NOVA University employees and assessed community mental health.Methods: Data were collected from voluntary participants at six NOVA University locations, in the Lisbon metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…During the first year of the pandemic, university employees had to fulfill new responsibilities that had repercussions not only on their workload but also on their mental health [7,9]. A number of different studies on this topic have shown that the increase in workload affected university employees by increasing their anxiety levels [24][25][26][27][28]. According to Santamaria et al [29], professors have experienced more anxiety since March 2020 due to their workload, the lack of clear instructions from their administration, the lack of access to personnel and resources, and a lack of knowledge and training related to online teaching and job insecurity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…During the first year of the pandemic, university employees had to fulfill new responsibilities that had repercussions not only on their workload but also on their mental health [7,9]. A number of different studies on this topic have shown that the increase in workload affected university employees by increasing their anxiety levels [24][25][26][27][28]. According to Santamaria et al [29], professors have experienced more anxiety since March 2020 due to their workload, the lack of clear instructions from their administration, the lack of access to personnel and resources, and a lack of knowledge and training related to online teaching and job insecurity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, according to Alfawaz et al [35], various sources of psychological stress led to severe depression in a considerable number of university employees, demonstrated by sleep problems, a lack of energy, and poor concentration [6,25,26,35]. Relationship problems at work were another factor that negatively affected the mental health of university employees by increasing their risk of anxiety, depression and insomnia, which in turn were detrimental to their quality of life at work [35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation